Short-lasting Unilateral Neuralgiform Headache Attacks with Conjunctival Injection and Tearing (SUNCT) sebagai Penyebab Nyeri Orbital Hebat pada Pasien Dewasa: Sebuah Laporan Kasus Komprehensif - Ahmad Dalma Haidar; Arda Fatkhul Khoiriyah (The Indonesian Journal of General Medicine, 2026)
Introduction: Short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) is an extremely rare trigeminal autonomic cephalalgia (TAC) characterized by highly frequent, ultra-brief, unilateral headache paroxysms accompanied by prominent ipsilateral cranial parasympathetic symptoms.1 Diagnosing SUNCT is clinically challenging due to substantial overlap with trigeminal neuralgia and other TACs, requiring meticulous evaluation and neuroimaging to exclude secondary structural etiologies.1 Case Illustration: A 47-year-old male presented with a 2-week history of excruciating, strictly right-sided orbital and supraorbital pain.4 The stabbing and burning paroxysms lasted 30-90 seconds, recurring 30-40 times daily, with an intensity of 9-10/10 on the Numeric Rating Scale (NRS).4 Attacks were triggered mechanically by touching the face, washing, or chewing, without any refractory period.4 Ipsilateral conjunctival injection, lakrimation, rhinorrhea, and marked psychomotor agitation consistently accompanied the pain.4 Neurological examination and non-contrast brain CT scan were normal.4 The patient was diagnosed with primary episodic SUNCT.4 A dual oral preventive therapy was immediately initiated with lamotrigine (25 mg/day, titrated up to 100 mg/day) and gabapentin (300 mg three times daily).4 At a 2-week follow-up, the daily attack frequency dramatically dropped to 5-7 times, and pain intensity significantly decreased to NRS 3-4/10, demonstrating excellent tolerability without adverse events.4 Discussion: SUNCT diagnosis relies on the ICHD-3 criteria.8 Pathophysiology involves central disinhibition of the trigemino-autonomic reflex and posterior hypothalamic activation.1 Although lamotrigine is the gold-standard first-line preventive, its mandatory slow titration creates a critical therapeutic gap during acute, high-frequency phases.5 The early addition of gabapentin provided a rapid, synergistic antinociceptive effect through dual-channel blockade of sodium and calcium channels, achieving swift pain control without dose-limiting toxicities.12 Conclusion: Combining lamotrigine and gabapentin represents a highly effective, safe, and easily accessible oral regimen for immediate and sustained control of high-frequency episodic SUNCT in clinical practice.4